The Yield of Ambulatory EEG-Video Monitoring. (July 2021) - Primiani, Christopher T.; Rivera-Cruz, Angélica; Trudeau, Pat; Sullivan, Lucy; MacIver, Stephanie; Benbadis, Selim R.
Introduction: The availability of ambulatory EEG-video monitoring gives an alternative to traditional inpatient EEG-video, but its yield and diagnostic value are not well known. This study evaluates the yield of ambulatory EEG-video for the diagnosis of epilepsy. Methods: We retrospectively reviewed the ambulatory EEG-video monitoring data from 200 consecutive and unselected patients aged 12 years and older performed by a single company (RSC Diagnostic Services) between January 2018 and May 2018. Studies were processed by two senior certified long-term monitoring EEG technologists and interpreted by neurologists. Results: Of the 200 patients, 130 (65%) were women, mean age was 45 years. Mean duration of studies were 76.6 hours (range 23-175 hours). There were 110 studies (55%) with events recorded and 101 (92%) were captured on video. Epileptic events accounted for 17.8% (18/101) of the events captured and 9% (18/200) of our total cohort. Nonepileptic diagnosis accounted for 38% of the total number of patients in study (76/200). Conclusion: Ambulatory EEG-video monitoring may be a useful alternative to inpatient epilepsy monitoring unit, particularly with high clinical suspicion for nonepileptic events.